PENGARUH BAGI HASIL DAN SUKU BUNGA BANK KONVENSIONAL PADA JUMLAH DEPOSITO MUDHARABAH - Mardianti, Amelia; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The research is meant to test the influence of profit sharing rates and interest rates bank konvensional to the amount of mudharabah deposit at Bank Mega Syariah in 2007-2014. This research uses quantitative. The data is the secondary data and time series which has been obtained from the financial statement of Bank Mega Syariah, the financial statistic of Bursa Efek Indonesia, and Bank Indonesia. The sampels are are quarterly financial statement from 2007 to 2014. The regressions analysis has been carried out in order to conduct significance test of the influenceof profit sharing rate and interest rate partially with the amount of mudharabah deposit.The result of the research has proved that: (a) profit sharing rate does not have any influence to the amount of mudharabah deposit; (b) interest rate bank konvensional has significant and positive influence to the amount of mudharabah deposit at Bank Mega Syariah because the rate of conventional bank increases, the amount of mudharabahi deposit does not experience any drestic changes because the customers still invest their fund at Bank Mega Syariah.Keywords: the amount of mudharabah deposit, profit sharing rate, interest rate.